A comparative study on interval arithmetic operations with intuitionistic fuzzy numbers for solving an intuitionistic fuzzy multi-objective linear programming problem - Vidhya, Rajendran; Irene Hepzibah, Rajkumar (Zielona Góra: Uniwersytet Zielonogórski)
In a real world situation, whenever ambiguity exists in the modeling of intuitionistic fuzzy numbers (IFNs), interval valued intuitionistic fuzzy numbers (IVIFNs) are often used in order to represent a range of IFNs unstable from the most pessimistic evaluation to the most optimistic one. IVIFNs are a construction which helps us to avoid such a prohibitive complexity.
Keywords: pentagonal intuitionistic fuzzy number; interval valued intuitionistic fuzzy number; interval valued intuitionistic fuzzy arithmetic; modified interval valued intuitionistic fuzzy arithmetic